Development of a computer vision pipeline for the analysis of Aliivibrio fischeri bioluminescence inhibition on solid media - Parker, Irshaad Ahmad (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc(Eng))--Stellenbosch University, 2023.